Faktor-Faktor yang Berpengaruh terhadap Praktik Masyarakat dalam Pengelolaan Sampah di Desa Ketenger, Kecamatan Baturaden, Kabupaten Banyumas - Widiyanto, Agnes Fitria; Zeha, Hamdan Nur; Rahardjo, Setiyowati; Suratman, Suratman (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2020)
Latar belakang: Sampah merupakan masalah yang sulit ditangani. Setiap tahun timbulan sampah semakin meningkat, sehingga diperlukan pengelolaan sampah untuk mengurangi masalah. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berpengaruh terhadap praktik masyarakat dalam pengelolaan sampah di Desa Ketenger, Kecamatan Baturaden, Kabupaten Banyumas.Metode: Jenis penelitian adalah analitik observasional dengan pendekatan crossectional, jumlah sampel 102 responden, pengambilan sampel dilakukan dengan metode Multistage Random Sampling, teknik pengumpulan data menggunakan kuesioner melalui wawancara.Kemudian, data dianalisis secara univariate, bivariate dan multivariate.Hasil: Sebagian besar responden memiliki praktik buruk sebanyak 59 responden (57,8%). Berdasarkan analisis multivariat, 2 variabel terkait adalah sikap (p = 0,001; Exp (B) = 5,378), infrastruktur (p = 0,001; Exp (B) = 6,402), dan keterpaparan media informasi (p = 0,003; Exp (B) = 4,215).Simpulan: Ada tiga variabel yang berpengaruh terhadap pengelolaan sampah yaitu sikap, sarana dan prasarana serta keterpaparan media informasi. Sarannya adalah memaksimalkan pengelolaan sampah di Desa Ketenger dengan prinsip 3 R (Reduce, Reuse and Recycle), baik oleh masyarakat atau oleh pemerintah desa setempat. ABSTRACTTitle: Factors that Influence Waste ManagementBackground: Solid waste is a problem which is not easy to be resolved. Amount of solid waste increases every year. Therefore, waste management is needed to solve the problem. The aim of this study was to identify factors influencing a community’s practice in managing waste at Ketenger Village, Baturraden Subdistrict, Banyumas Regency.Methods: This was an analytic observational study using a cross sectional approach. As many as 102 respondents were selected using a technique of Multistages Random Sampling. Data were collected by conducting interview using a questionnaire. Furthermore, data were analysed using methods of univariate, bivariate, and multivariate analyses.Result: more than half of the respondents (59 persons or 57.8%)had a poor practice. Based on the multivariate analysis, threeinfluenced variables were attitudes (p = 0.001; Exp (B) = 5.378), infrastructure (p = 0.001; Exp (B) = 6.402), and information media exposure (p = 0.003; Exp (B) = 4.215).Conclusion: the variables influencing a community’s practice in managing waste were attitude and infrastructure. As a suggestion, to improve waste management in Ketenger Village, the principles of 3R (Reduce, Reuse and Recycle) need to be applied either by the community or by the village government. ABSTRACTTitle: Factors that Influence Waste ManagementBackground: Solid waste is a problem which is not easy to be resolved. Amount of solid waste increases every year. Therefore, waste management is needed to solve the problem. The aim of this study was to identify factors influencing a community’s practice in managing waste at Ketenger Village, Baturraden Subdistrict, Banyumas Regency.Methods: This was an analytic observational study using a cross sectional approach. As many as 102 respondents were selected using a technique of Multistages Random Sampling. Data were collected by conducting interview using a questionnaire. Furthermore, data were analysed using methods of univariate, bivariate, and multivariate analyses.Result: more than half of the respondents (59 persons or 57.8%)had a poor practice. Based on the multivariate analysis, threeinfluenced variables were attitudes (p = 0.001; Exp (B) = 5.378), infrastructure (p = 0.001; Exp (B) = 6.402), and information media exposure (p = 0.003; Exp (B) = 4.215).Conclusion: the variables influencing a community’s practice in managing waste were attitude and infrastructure. As a suggestion, to improve waste management in Ketenger Village, the principles of 3R (Reduce, Reuse and Recycle) need to be applied either by the community or by the village government.